Functional dissociation of transient and sustained fMRI BOLD components in human auditory cortex revealed with a streaming paradigm based on interaural time differences - Schadwinkel, Stefan; Gutschalk, Alexander (European journal of neuroscience, 2010)
A number of physiological studies suggest that feature-selective adaptation is relevant to the pre-processing for auditory streaming, the perceptual separation of overlapping sound sources. Most of these studies are focused on spectral differences between streams, which are considered most important for streaming. However, spatial cues also support streaming, alone or in combination with spectral cues, but physiological studies of spatial cues for streaming remain scarce. Here, we investigate whether the tuning of selective adaptation for interaural time differences (ITD) coincides with the range where streaming perception is observed. FMRI activation that has been shown to adapt depending on the repetition rate was studied with a streaming paradigm where two tones were differently lateralized by ITD. Listeners were presented with five different ΔITD conditions (62.5, 125, 187.5, 343.75, or 687.5 μs) out of an active baseline with no ΔITD during fMRI. The results showed reduced adaptation for conditions with ΔITD ≥ 125 μs, reflected by enhanced sustained BOLD activity. The percentage of streaming perception for these stimuli increased from approximately 20% for ΔITD = 62.5 μs to > 60% for ΔITD = 125 μs. No further sustained BOLD enhancement was observed when the ΔITD was increased beyond ΔITD = 125 μs, whereas the streaming probability continued to increase up to 90% for ΔITD = 687.5 μs. Conversely, the transient BOLD response, at the transition from baseline to ΔITD blocks, increased most prominently as ΔITD was increased from 187.5 to 343.75 μs. These results demonstrate a clear dissociation of transient and sustained components of the BOLD activity in auditory cortex.
Gesehen am 09.08.2023